Melawan Otoritarianisme Digital di Indonesia: Urgensi Reformasi Hukum dan Perlindungan Hak Digital dalam Era Represi 2025 - Abi, Kemal; Ikbal, Ikbal; Alif, Sayyid; Jueni, Jueni; Endarto, Dwi Wahyu; Adi Candra, Firman (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research examines the escalating phenomenon of digital authoritarianism in Indonesia in 2025, characterized by increased digital repression and human rights violations in cyberspace. Employing a descriptive qualitative approach, this article analyzes trends in the use of regulations such as the Electronic Information and Transactions Law (ITE Law) as a tool for repression, restrictions on freedom of expression, data surveillance, and the criminalization of activists and journalists. Significant impacts on civil and political liberties, as well as the vulnerability of minority groups, women, and children, are key highlights. The study emphasizes the urgency of legal reform, including the harmonization of regulations with international human rights principles such as the International Covenant on Civil and Political Rights (ICCPR), and the importance of public participation in legislation. Furthermore, this article offers digital rights protection strategies involving the role of civil society, digital literacy education, multi-stakeholder collaboration, and policy advocacy to counter digital authoritarianism for a just democracy. The research also explores concrete case studies, such as Amnesty International's report on